Pre-Service Physics Teachers' Self-Assessment of Professional Competence After Following PPG (Teacher Professional Education) - Habibah Khusna Baihaqi; Dyah Arum Arimurti (Universitas Sebelas Maret, 2025)
This study aimed to evaluate the effectiveness of the Physics TPE program in improving teacher professionalism by considering the perceptions of its graduates. Data were collected through a self-assessment questionnaire/survey given to Physics TPE graduates regarding their teacher professional competence before and after participating in TPE. A total of 36 physics TPE graduates participated in this study. The results showed significant improvements in various aspects of teacher professionalism. Graduates reported improvements in their mastery of educational foundations, teaching program preparation, teaching program implementation, assessment, and student character building. In particular, the greatest improvement was observed in mastery of educational foundations, likely due to the alignment of the TPE curriculum with the stages of effective teaching. While teaching implementation showed the smallest improvement, it was still positive. Overall, the Physics TPE program was perceived well by its graduates, indicating its potential to contribute to the professional development of physics teachers.